Comparison of hemodynamic responses between normotensive and untreated hypertensive men under simulated long working hours - Hiroki Ikeda; Xiaoqin Liu; Fuyuki Oyama; Keiko Wakisaka; Masaya Takahashi (Nordic Association of Occupational Safety and Health (NOROSH), 2018)
OBJECTIVES: The present study examined hemodynamic responses of normotensive and untreated hypertensive participants under simulated long working hours (LWH) - 13 hours - in an experimental laboratory study. METHODS: Thirty-five men participated in this study. Twenty-two of these participants were categorized into the normotensive group (systolic blood pressure (SBP) ≤140 mmHg and diastolic blood pressure (DBP) ≤90 mmHg); one participant was excluded due to missing data, leaving twenty-one participants with a mean age of 49.2 years. Another thirteen participants were categorized into the high blood pressure group (SBP=140-160 mmHg or DBP=90-100 mmHg) with a mean age of 51.9 years. The hemodynamic responses at the resting state from 09:00-09:10 hours (baseline) and during LWH from 09:10-22:00 hours (12 sessions) were measured. In each session, participants performed mental tasks. Changes in the hemodynamic response (Δ) were calculated by subtracting the individual values at each session from the baseline values. RESULTS: The values for the ΔSBP, ΔDBP, and Δmean arterial pressure increased with work time. Additionally, we found a significant interaction between the group and sessions for the ΔSBP (P<0.05, partial η^2=0.086). Although ΔSBP values did not differ between the groups at first (09:10-14:30 hours), the values in later sessions (14:40-21:50 hours) were significantly higher in the high blood pressure compared to the normotensive group. CONCLUSIONS: Our study found that LWH increases BP, with a larger increase in SBP in the later working hours among individuals with untreated hypertension, whereas other hemodynamic responses did not differ between groups as a function of the LWH.